Konsepsi Kepemimpinan Kepala Sekolah (Analisis Fungsi Kepala Sekolah Sebagai Pengembangan Pembelajaran PAI) - Noor Fatikah; Fitriatul Jannah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2018)
The leaders’ existence in conducting their function facing the change occured in their schools by stating the aim, making their deputy function through partisipative approach, based on their leader capability professionally. The head master as an influential person in developing or decreasing educational institution including Islamic educational subject have to be able to run their tasks as educator, manager, administrator, supervisor, leader, innovator and motivator. The head master leadership analysis as developer of PAI learning, if they can run their function as supervisor, leader, innovator in learning PAI policy. The school success in reaching out the PAI learning aim based on the leader capability in running their school. Their role influences to create the purposes has been decided. That is why the organization success in acheiving puposes based on the successful of their leader.